Transcriptome analysis of messenger RNA and long noncoding RNA related to different developmental stages of tail adipose tissues of sunite sheep. Issue 10 (25th August 2021) - He, Xige; Wu, Rihan; Yun, Yueying; Qin, Xia; Chen, Lu; Han, Yunfei; Wu, Jindi; Sha, Lina; Borjigin, Gerelt
Abstract: The tail fat of sheep is the most typical deposited fat, and it can be widely used in human daily life, such as diet, cosmetics, and industrial raw materials. To understand the potential regulatory mechanism of different growth stages of tail fat in Sunite sheep, we performed high‐throughput RNA sequencing to characterize the long noncoding RNA (lncRNA) and messenger RNA (mRNA) expression profiles of the sheep tail fat at the age of 6, 18, and 30 months. A total of 223 differentially expressed genes (DEGs) and 148 differentially expressed lncRNAs were found in the tail fat of 6‐, 18‐, and 30‐month‐old sheep. Based on functional analysis, we found that fat‐related DEGs were mainly expressed at 6 months of age and gradually decreased at 18 and 30 months of age. The target gene prediction analysis shows that most of the lncRNAs target more than 20 mRNAs as their transregulators. Further, we obtained several fat‐related differentially expressed target genes; these target genes interact with different differentially expressed lncRNAs at various ages and play an important role in the development of tail fat. Based on the DEGs and differentially expressed lncRNAs, we established three co‐expression networks for each comparison group. Finally, we concluded that the development of the sheep tail fat is more active during the early stage of growth and gradually decreases with the increase in age. The mutual regulation of lncRNAs and mRNAs may play a key role in this complex biological process. Abstract : The mRNA and lncRNA expression profiles were characterized in three different growth stages of Sunite sheep fat tail tissue. The development of sheep tail fat is more active in the early stage and gradually decreases with the increase of age. LncRNA may regulate the development of Sunite sheep tail fat mainly through positive correlation with multiple mRNAs.